Upregulation of miR150-5p in generalized myasthenia gravis patients is associated with decreased serum levels of IL-17 and increased serum levels of IL-10 - Ao, Wenling; Tian, Canhui; He, Xiongjun; Hu, Yeli; Wang, Weidong; Liu, Yajie (Biomedical papers, 2020)
Background: MiR150-5p has been reported to be involved in generalized myasthenia gravis, in which different cytokines play critical roles. The regulatory network of cytokines in generalized myasthenia gravis has not been fully elucidated. Our study aimed to investigate the interactions between miR150-5p and different cytokines in generalized myasthenia gravis. Materials and Method. Serum levels of miR150-5p and different cytokines including IL-2, IL-17, IL-10, IL-19, IL-20 and IL-35 were detected by qRT-PCR and ELISA, respectively. ROC curve analysis was performed to evaluate the diagnostic value of miR150-5p for generalized myasthenia gravis. Correlation between serum levels of miR150-5p and different cytokines were analyzed by Pearson correlation coefficient. Results: Compared with healthy controls, decreased serum levels of IL-2 and IL-17 and increased serum levels of miR150-5p, IL-10, IL-19, IL-20 and IL-35 were observed in patients with generalized myasthenia gravis. Serum levels of miR150-5p were positively correlated with IL-10 and negatively correlated with IL-17. After treatments, serum levels of miR150-5p and IL-10 decreased, while serum levels of IL-2 and IL-17 increased. Conclusion: Upregulation of miR150-5p is involved in generalized myasthenia gravis patients and is associated with decreased serum levels of IL-17 as well as increased serum levels of IL-10.
Keywords: generalized myasthenia gravis; MiR150-5p; cytokines